A high-porosity interpenetrating network structure gel powder and its preparation method and application
By using high porosity interpenetrating network structure gel powder in water-based polyurethane coatings, an interpenetrating network structure between nanocellulose and polyimide nanofibers is formed, and the problems of insufficient corrosion resistance and low mechanical properties of water-based polyurethane coatings are solved, and better mechanical properties and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411699764.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Water-based polyurethane coatings have problems such as insufficient corrosion resistance, bubble formation and weak intermolecular forces in industrial applications, resulting in low mechanical properties, limiting their wide application.
The aqueous polyurethane coating is modified by a high-porosity interpenetrating network structure gel powder. By injecting the polyamic acid mixed solution into the nanocellulose hydrogel solution under stirring conditions, an interpenetrating network structure is formed, which improves the porosity of the gel and the interaction degree of fibers.
It significantly improves the adhesion, flexibility and acid and alkali salt resistance of the polyurethane coating, enhances the mechanical properties and corrosion resistance of the coating, and solves the problem of poor compatibility of water-based polyurethane coatings.
Smart Images

Figure CN119192665B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of honeycomb materials, and in particular relates to a high-porosity interpenetrating network structure gel powder, a preparation method and application thereof. Background Art
[0002] Polyurethane can be divided into two categories: solvent-based polyurethane and water-based polyurethane (WPU) due to its different dispersion medium. Water-based polyurethane is a polyurethane emulsion in which polyurethane resin uses water as the dispersion medium. In terms of structure, the rigid chain segment with ionic groups is hydrophilic, while the flexible chain segment plays a hydrophobic role; in terms of performance, it has the excellent characteristics of polyurethane resin. In terms of environmental impact, water-based polyurethane basically contains no or only trace amounts of organic compounds, and has the characteristics of being green, safe and non-toxic, low in manufacturing cost, and having many application fields. The demand for non-toxic, non-flammable and air-free resins has promoted the rapid development of water-based polyurethane.
[0003] The structure of waterborne polyurethane is a segmented polymer composed of soft segments and hard segments. Its performance is affected by its composition structure. The soft segments and hard segments form a unique separated microphase, which is the separated microphase that gives it many properties. Waterborne polyurethane has important application prospects in many industrial applications, such as coatings, adhesives, inks, glass fibers, paper pulp, synthetic leather, biomaterials, membranes and packaging films, and waterproof textiles.
[0004] The soft segment structure of waterborne polyurethane is composed of oligomer polyols, which have a great influence on its water resistance and mechanical strength. The hard segment structure is composed of isocyanate and small molecule chain extender, which has a great influence on the hardness, emulsion particle size and bonding performance of waterborne polyurethane after film formation. The structure of waterborne polyurethane can be adjusted in production. The soft segment provides flexibility and the hard segment provides rigidity. The main factors affecting its performance are the hydrogen bonds between hard-soft segments and hard-hard segments. With the increase of soft segment content, the degree of polymer crystallization and tensile properties are improved, but polyols are easily hydrolyzed, which will lead to poor water resistance. If you want to improve the hardness and bonding strength of waterborne polyurethane, you can increase the hard segment content appropriately, but if the hard segment content is too high, it will increase the chemical inertness of the chain segment, hinder the diffusion of molecular links, and lead to reduced bonding strength.
[0005] Waterborne polyurethane coatings not only require high gloss, color retention, scratch resistance and flame retardancy, but also protect materials from moisture, biological and chemical erosion. They are green, safe and pollution-free, and are often used in the fields of automobiles, construction, wood, paper, leather, and fabric coatings. However, waterborne polyurethane coatings use water as a carrier, and their lack of corrosion resistance is their biggest disadvantage, which to a certain extent affects their application in the industrial field. In addition, there are many problems in practical applications, such as a large number of bubbles generated during the reaction with water, which are difficult to eliminate and may remain in the coated film, affecting the various properties of the film. At the same time, due to their low solid content and weak intermolecular forces, the mechanical properties of waterborne polyurethane coatings are usually lower than those of traditional solvent-based polyurethane coatings, which has become a key bottleneck restricting their widespread application.
[0006] Blending modification is to physically blend the prepared WPU emulsion with other types of emulsions or some nanomaterials, and evenly disperse them through mechanical stirring or ultrasonic dispersion, so as to prepare the required functional coating. Nanomaterials refer to materials that have at least one dimension in the nanoscale range in three-dimensional space or are composed of them as basic units. Adding nanoparticles to polymers is one of the important methods to improve the performance of polymer materials. At present, there are many nanomaterials used to enhance and improve waterborne polyurethane, mainly including: nanocellulose, nanometal particles, nanocarbon materials, nanooxides, etc. CN118852963A discloses a heat-reflecting heat-insulating coating, in which nano-titanium dioxide is evenly dispersed in a cellulose aerogel matrix and a polyurethane coating, and the aggregation of nano-titanium dioxide is inhibited. The cellulose aerogel improves the flame retardant properties of the coating. CN117801653A discloses a highly elastic hydrophobic radiation-cured wood lacquer skin-feel coating, and the addition of hyperbranched nanocellulose hydrogel realizes the skin-tactile properties of the coating on the wood surface, and the physical and mechanical properties and durability of the coating are improved by reacting the -NH2 group in the hyperbranched nanocellulose hydrogel and the -NCO group in the radiation light-cured coating. CN110105531A and CN107474680A also disclose adding gel materials to the coating to improve the corresponding properties of the coating. However, the above-mentioned technology is only to add modified cellulose gel. As a natural fiber material, the mechanical properties of cellulose gel are relatively low; and cellulose gel has a large specific surface area. Due to the interaction between molecules and the influence of hydrogen bonds, cellulose gel is easily aggregated, so that its dispersibility and stability in polyurethane coatings are poor. At the same time, since the process of preparing cellulose gel is relatively complicated, the cost is high, and the yield is low, it is not suitable for large-scale industrialization. Summary of the invention
[0007] The purpose of the present invention is to provide a high-porosity interpenetrating network structure gel powder and its preparation method and application. The gel powder is used to modify the polyurethane coating, so that the polyurethane coating can fully infiltrate the inside of the gel, improve the interaction between the gel powder and the polyurethane, so that the obtained polyurethane coating has high adhesion, good flexibility, and excellent acid, alkali and salt resistance.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0010] (1) treating natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose;
[0011] (2) preparing a nanocellulose hydrogel solution by preparing a nanocellulose deionized water dispersion;
[0012] (3) preparing a polyamic acid solution in an organic solvent using diamine and dianhydride as raw materials, then adding polyvinyl pyrrolidone and stirring to obtain a polyamic acid mixed solution; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is (0.01-0.5):1;
[0013] (4) Under stirring conditions, injecting the polyamic acid mixed solution into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, adding a chemical imidization reagent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure;
[0014] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0015] Cellulose is a common high molecular polymer in nature, widely found in plants such as cotton, hemp and wood, and has the advantages of good biocompatibility, renewability, biodegradability, environmental friendliness and non-toxicity. Nanocellulose is made from cellulose, and has at least one dimensional space size of less than 100nm. Nanocellulose composite hydrogel materials not only retain the unique physical and chemical properties of cellulose, such as hydrophilicity, biocompatibility, biodegradability, high chemical activity and dimensional stability, but also have new structural characteristics given by micro-nano processing technology, such as light weight, softness, high specific surface area, high crystallinity, high strength, high modulus and mild chemical activity. Because the surface of cellulose nanofibers has abundant hydroxyl groups, cellulose exhibits high hydrophilicity, and can quickly form a uniform and stable nanocellulose suspension in the coating, which is widely used.
[0016] However, nanocellulose has low mechanical properties and has limited performance improvement on the coating. In addition, due to its large specific surface area and strong hydrogen bonding, nanocellulose is prone to agglomeration, and has poor compatibility with the matrix and uneven dispersion. In previous works (CN118667223A, CN118812911A, CN118702962A, etc.), the inventors first prepared hydrogels and then directly added fibrous fillers or water-soluble polyamic acid salts. In this method, the fibrous fillers can only be dispersed outside the hydrogel and cannot penetrate into the gel to form an interpenetrating structure. The water-soluble polyamic acid salts cannot be precipitated into fibrous structures.
[0017] In order to solve the problems existing in nanocellulose, the present invention first prepares nanocellulose gel, and then prepares polymer nanofibers through a precipitation process. The precipitation method is a common process for preparing polymer nanofibers in the prior art, but directly pouring polyamic acid into the precipitation liquid will obtain micron or even millimeter-sized fibers, and nanometer-sized fiber structures cannot be prepared.
[0018] The present invention injects a polyamic acid mixed solution into a nanocellulose hydrogel solution under stirring. Among them, nanocellulose not only plays a role in forming an interpenetrating network structure; more importantly, under rapid stirring, the nanocellulose fibers in the solution can play a "sickle"-like splitting role, so that the polyamic acid mixed solution is split into bundles with smaller diameters, thereby reducing the diameter of the polyamic acid fibers. In order to further make the fiber diameter reach the nanometer level, and also to enable the polyamic acid solution to form a stable bundle structure in the rapidly stirred nanocellulose hydrogel solution, the generation of the nanofiber structure is promoted. The present invention adds a certain amount of polyvinyl pyrrolidone. On the one hand, the polyvinyl pyrrolidone molecule contains a pyridine ring structure, which can form a hydrogen bond with the imine structure and carboxyl group on the polyamic acid, provide an adsorption force, and enable the organic solution "bundle" of the polyamic acid to be stably dispersed in the nanocellulose hydrogel solution; on the other hand, polyvinyl pyrrolidone also has a hydrophilic effect, and can hydrate with water molecules in the nanocellulose hydrogel solution. When the polyamic acid mixed solution is injected into the nanocellulose hydrogel solution, the adsorption force and hydration force of polyvinyl pyrrolidone cause polyvinyl pyrrolidone to disperse in the outer surface of the organic solution "tow" of polyamic acid. Since polyvinyl pyrrolidone itself has a high viscosity, it can promote the stability of the "tow" structure. Under the shear force provided by stirring and the "cutting" effect of nanocellulose, the "tow" can gradually become longer and thinner, thereby increasing the aspect ratio of the polyimide fiber and promoting the formation of the nanofiber structure. The molecular weight of polyvinyl pyrrolidone is not particularly limited, and its specific number average molecular weight can be 8000-200000.
[0019] The precipitation method is a common method for preparing polyimide fibers. During the forming process of the precipitated fiber, the polyamic acid droplets enter the shear-flowing precipitating agent. Under the action of the shear force, the polyamic acid droplets are stretched and elongated. At the same time, the organic solvent in the polyamic acid droplets and the coagulant water in the precipitating agent perform a double diffusion effect, and the polyamic acid fiber is gradually precipitated. The inventor also used the drop method to prepare polyimide precipitated nanofibers in previous work. However, when the polyimide nanofiber is prepared by the drop method, the drop size is difficult to control, and the droplet contacts the nanocellulose gel aqueous solution at the liquid surface with a spherical structure, and the contact area between the droplet and the precipitated solution is small; more importantly, the splitting effect of the nanocellulose at the liquid surface is difficult to give full play, so that the prepared polyimide nanofiber has a low degree of interaction with the nanocellulose, and the gel powder has a low porosity, which is not conducive to the full infiltration of water-based polyurethane. In order to improve the degree of interaction between polyimide nanofibers and nanocellulose, the present invention adopts an injection method to prepare precipitated fibers. Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution. The polyamic acid solution added by injection can make the solution contact with the precipitate in a fine filamentous structure. Compared with the droplets formed by the dripping method, the contact area with the precipitate is greatly increased, and the precipitated polyamic acid fibers have better dispersion. Moreover, since the nozzle is inside the nanocellulose hydrogel solution, the splitting effect of the nanocellulose fibers is more fully exerted, so that the polyamic acid mixed solution is split into filaments with smaller diameters, further reducing the diameter of the polyamic acid fibers.
[0020] In general, the internal injection method can increase the contact area between the polyamic acid solution and the precipitate. During the stirring process, under the breaking effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the polyamic acid mixed solution can form fine liquid flows in the stirred nanocellulose hydrogel solution and gradually precipitate to form polyamic acid nanofibers, thereby forming an interpenetrating network structure with nanocellulose, greatly improving the porosity of the gel and the degree of interaction between the fibers.
[0021] This composite functional gel material not only retains the original properties of the gel material, but also combines the high modulus, high strength, thermal stability, high chemical activity and other properties of nanocellulose and polyimide nanofibers with the solution properties of hydrogels, making up for the "soft and weak" defects of nanocellulose gel materials in mechanical structure, and laying the foundation for potential application development of gels.
[0022] Furthermore, in step (1), the natural cellulose raw material is at least one of cotton, bamboo powder, waste paper, flax, sisal, straw, and bagasse; the treatment method includes at least one of high-pressure homogenization, acid hydrolysis, enzymatic hydrolysis, and TEMPO oxidation; the diameter of the nanocellulose is 10-100nm and the length is 5-20μm. Furthermore, the nanocellulose of the present invention is prepared by TEMPO oxidation. The full name of TEMPO is 2,2,6,6-tetramethylpiperidinyl oxide, which is an organic nitrogen oxide with weak oxidizing properties. This method has a short reaction time, is non-toxic, and has a low cost, and the morphology and size of the prepared nanocellulose are relatively uniform. By controlling the process parameters of the TEMPO oxidation method, the aspect ratio of the nanocellulose can be effectively adjusted and the degree of interaction between the nanocellulose and the polyimide nanofiber can be improved.
[0023] Furthermore, in step (2), a nanocellulose hydrogel solution is prepared by a steam bath method or an ion crosslinking method. The steam bath method is to place a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution. The acidic steam bath is at least one of a formic acid steam bath, an acetic acid steam bath, a hydrochloric acid steam bath, and a nitric acid steam bath; and the steam bath treatment time is 2-10 hours. The ion crosslinking method is to add a solution containing metal ions to a deionized water dispersion of nanocellulose under stirring conditions, and obtain a nanocellulose hydrogel solution after sol gelation. The metal ion is Li + 、Na + , K + , Ca 2+ Mg 2+ 、Zn 2+ , Cu 2+ 、Al 3+ The metal ion source is at least one of the chloride, sulfate, carbonate or nitrate corresponding to the metal. The mass ratio of the metal ion to the mass of the nanocellulose is (0.01-0.1):1.
[0024] Furthermore, the nanocellulose content in the nanocellulose hydrogel solution in step (2) is 0.5-2wt%.
[0025] Furthermore, in step (3), the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is (0.5-3):1; and the content of polyamic acid in the polyamic acid mixed solution is 2-6wt%.
[0026] Furthermore, in step (4), the nozzle has 1-4 nozzles. By injecting the polyamic acid solution through the nozzles provided on the nozzle, the injection rate can be adjusted by the number of nozzles and the size of the nozzle aperture; compared with the dripping method, the addition rate and morphology of the polyamic acid solution are easier to control. There is no particular limitation on the number and aperture of the nozzles on the nozzle, and they can be adjusted according to the required injection rate. In particular, when multiple nozzles are used, the nozzles are evenly distributed on the nozzles. Evenly distributed nozzles are more conducive to the uniform injection of the polyamic acid solution into the nanocellulose gel solution, and the nanocellulose fibers can fully play a splitting role, so that the polyamic acid mixed solution is split into bundles with smaller diameters, thereby reducing the diameter of the polyamic acid fibers.
[0027] Furthermore, in step (4), the nozzle aperture is 0.1-1 mm. Furthermore, the number of nozzles is 1, and the nozzle aperture is 0.3 mm. Furthermore, a 1 ml or 2 ml syringe commonly used on the market can be selected for injection.
[0028] Furthermore, in step (4), the injection rate of the polyamic acid mixed solution is 1-3 mL / min. Furthermore, the injection rate is 1.8-2.4 mL / min. By adjusting the injection rate, the polyamic acid mixed solution can be fully dispersed into the nanocellulose hydrogel solution, and the splitting effect of the nanocellulose can be fully exerted.
[0029] Furthermore, in step (3), the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is (0.5-3):1; further, the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is (1-1.5):1. The types of diamine and dianhydride are not particularly limited, and the molar ratio of dianhydride monomer to diamine monomer is 1:(0.95-1.05); the organic solvent used in the reaction is at least one of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide. Specifically, the dianhydride monomer is at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, hexafluoro dianhydride, and 3,3',4,4'-benzophenone tetracarboxylic dianhydride; the diamine monomer is at least one of 4, 4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, and p-phenylenediamine.
[0030] Furthermore, in step (4), the stirring rate is 400-900 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of (1-3):1, and the mass of the mixture is 10-30% of the mass of the polyamic acid solution. Furthermore, in step (4), the stirring rate is 600-700 rpm. An appropriate stirring rate can avoid the reduction of the aspect ratio of the polyimide nanofibers due to too fast stirring rate, and can also prevent the defect of a thicker diameter due to too slow stirring rate.
[0031] On the other hand, the present invention also provides an application of the high-porosity interpenetrating network structure gel powder, and the high-porosity interpenetrating network structure gel powder is used in the field of polyurethane coatings.
[0032] The polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion; and 0.5-5 parts of the gel powder having an interpenetrating network structure with high porosity.
[0033] The interpenetrating network structure gel powder prepared by injection method can make the nanocellulose and polyimide nanofibers fully interact with each other, and the gel structure is more regular and the porosity is higher. The higher porosity is conducive to the full infiltration of polyurethane, and improves the bonding force between the gel powder and the polyurethane coating, thereby further improving the mechanical properties and anti-corrosion ability of the coating. Moreover, the large number of hydroxyl groups on the surface of the nanocellulose in the gel powder will hydrogen bond with the polyurethane matrix molecules, which enhances the interfacial interaction between the gel powder and the polyurethane matrix, and solves the technical problem of poor compatibility between polyimide nanofibers and polyurethane coatings. Polyimide nanofibers have high mechanical properties, which solves the "soft and weak" defect of nanocellulose gel materials in mechanical structure. Nanocellulose and polyimide nanofibers form an interpenetrating structure, which makes the two fully entangled, exerts a synergistic reinforcement effect, and improves the density and mechanical properties of the polyurethane coating.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The interpenetrating network structure gel powder prepared by the injection method can make the nanocellulose and polyimide nanofibers fully interact with each other, making the gel structure more regular and having a higher porosity. The higher porosity is conducive to the full infiltration of polyurethane, improving the bonding force between the gel powder and the polyurethane coating, thereby further improving the mechanical properties and anti-corrosion ability of the coating.
[0036] (2) First, prepare nanocellulose hydrogel and construct nanocellulose-based gel material, and then inject the polyamic acid mixed solution into the nanocellulose hydrogel solution under stirring. Under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the polyamic acid mixed solution can form fine liquid flows in the stirred nanocellulose hydrogel solution and gradually precipitate to form polyamic acid nanofibers, thereby forming an interpenetrating network structure with nanocellulose.
[0037] (3) Hydrogen bonds will occur between the nanocellulose in the gel powder and the polyurethane matrix molecules, solving the technical problem of poor compatibility between polyimide nanofibers and polyurethane coatings. Polyimide nanofibers solve the "soft and weak" defect of nanocellulose gel materials in mechanical structure. Nanocellulose and polyimide nanofibers form an interpenetrating structure, and the two play a synergistic role in improving the density and mechanical properties of the polyurethane coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 A simple injection device used in the present invention;
[0039] Figure 2 This is a scanning electron microscope image of the gel powder prepared in Example 11;
[0040] Figure 3 This is a scanning electron microscope image of the gel powder prepared in Comparative Example 1. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application. If not otherwise specified, the preparation raw materials and process conditions in the following examples and comparative examples are all consistent.
[0042] Example 1
[0043] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0044] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0045] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 4 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 0.5wt%;
[0046] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.04:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.3:1; the polyamic acid content in the polyamic acid mixed solution is 2wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:0.95; the organic solvent is N-methylpyrrolidone; the dianhydride monomer is pyromellitic dianhydride; and the diamine monomer is 4, 4'-diaminodiphenyl ether;
[0047] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 1.8 mL / min; the stirring rate is 400 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 1:1, and the mass of the mixture is 10% of the mass of the polyamic acid solution;
[0048] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0049] A polyurethane coating comprises the following components in parts by weight:
[0050] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0051] Example 2
[0052] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0053] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0054] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is an acetic acid steam bath; the steam bath treatment time is 8 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 2wt%;
[0055] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.5:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.8:1; the polyamic acid content in the polyamic acid mixed solution is 6wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:1.04; the organic solvent is a mixture of N-methylpyrrolidone and dimethylacetamide in a volume ratio of 1:1; the dianhydride monomer is a mixture of pyromellitic anhydride and 3,3',4,4'-biphenyltetracarboxylic anhydride in a molar ratio of 3:1; the diamine monomer is 4, 4'-diaminodiphenyl ether;
[0056] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 2.4 mL / min; the stirring rate is 900 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 3:1, and the mass of the mixture is 30% of the mass of the polyamic acid solution;
[0057] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0058] A polyurethane coating comprises the following components in parts by weight:
[0059] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0060] Example 3
[0061] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0062] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0063] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is a hydrochloric acid steam bath; the steam bath treatment time is 4 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 2wt%;
[0064] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.07:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.8:1; the polyamic acid content in the polyamic acid mixed solution is 3wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent is dimethylformamide; the dianhydride monomer is 3,3',4,4'-biphenyltetracarboxylic dianhydride; the diamine monomer is a mixture of 4,4'-diaminodiphenyl ether and p-phenylenediamine in a molar ratio of 1:1;
[0065] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 2.4 mL / min; the stirring rate is 900 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 3:1, and the mass of the mixture is 12% of the mass of the polyamic acid solution;
[0066] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0067] A polyurethane coating comprises the following components in parts by weight:
[0068] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0069] Example 4
[0070] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0071] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0072] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 5 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 1wt%;
[0073] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.1:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.4:1; the polyamic acid content in the polyamic acid mixed solution is 3wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:0.98; the organic solvent is dimethylacetamide; the dianhydride monomer is a mixture of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride and hexafluorodianhydride in a molar ratio of 1:1; the diamine monomer is 4,4'-diaminodiphenylmethane;
[0074] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with an aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 1.9 mL / min; the stirring rate is 500 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 1.5:1, and the mass of the mixture is 15% of the mass of the polyamic acid solution;
[0075] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0076] A polyurethane coating comprises the following components in parts by weight:
[0077] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0078] Example 5
[0079] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0080] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0081] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is an acetic acid steam bath; the steam bath treatment time is 7 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 1.7 wt%;
[0082] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.4:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.7:1; the polyamic acid content in the polyamic acid mixed solution is 5wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:1.03; the organic solvent is a mixture of N-methylpyrrolidone and dimethylacetamide in a volume ratio of 1:1; the dianhydride monomer is 3,3',4,4'-benzophenonetetracarboxylic dianhydride; the diamine monomer is 4, 4'-diaminodiphenyl ether;
[0083] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 2.2 mL / min; the stirring rate is 800 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 2.5:1, and the mass of the mixture is 25% of the mass of the polyamic acid solution;
[0084] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0085] A polyurethane coating comprises the following components in parts by weight:
[0086] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0087] Example 6
[0088] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0089] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0090] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is a formic acid steam bath; the steam bath treatment time is 6 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 0.9wt%;
[0091] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.6:1; the polyamic acid content in the polyamic acid mixed solution is 2wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:1; the organic solvent is N-methylpyrrolidone; the dianhydride monomer is a mixture of pyromellitic dianhydride and 3,3',4,4'-benzophenonetetracarboxylic dianhydride in a molar ratio of 1:1; the diamine monomer is a mixture of 4, 4'-diaminodiphenyl ether and p-phenylenediamine in a molar ratio of 1:1;
[0092] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 2.1 mL / min; the stirring rate is 600 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 1.5:1, and the mass of the mixture is 18% of the mass of the polyamic acid solution;
[0093] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0094] A polyurethane coating comprises the following components in parts by weight:
[0095] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0096] Example 7
[0097] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0098] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0099] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is an acetic acid steam bath; the steam bath treatment time is 7 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%;
[0100] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 0.5:1; the polyamic acid content in the polyamic acid mixed solution is 4wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent is a mixture of N-methylpyrrolidone and dimethylformamide in a volume ratio of 1:1; the dianhydride monomer is a mixture of pyromellitic anhydride and 3,3',4,4'-biphenyltetracarboxylic anhydride in a molar ratio of 2:1; the diamine monomer is 4,4'-diaminodiphenylmethane;
[0101] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with an aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 2 mL / min; the stirring rate is 700 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;
[0102] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0103] A polyurethane coating comprises the following components in parts by weight:
[0104] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0105] Example 8
[0106] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0107] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0108] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is an acetic acid steam bath; the steam bath treatment time is 7 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%;
[0109] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 3:1; the polyamic acid content in the polyamic acid mixed solution is 4wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent is a mixture of N-methylpyrrolidone and dimethylformamide in a volume ratio of 1:1; the dianhydride monomer is a mixture of pyromellitic anhydride and 3,3',4,4'-biphenyltetracarboxylic anhydride in a molar ratio of 2:1; the diamine monomer is 4,4'-diaminodiphenylmethane;
[0110] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with an aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 2 mL / min; the stirring rate is 700 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;
[0111] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0112] A polyurethane coating comprises the following components in parts by weight:
[0113] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0114] Example 9
[0115] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0116] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0117] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is an acetic acid steam bath; the steam bath treatment time is 7 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%;
[0118] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.5:1; the polyamic acid content in the polyamic acid mixed solution is 4wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent is a mixture of N-methylpyrrolidone and dimethylformamide in a volume ratio of 1:1; the dianhydride monomer is a mixture of pyromellitic anhydride and 3,3',4,4'-biphenyltetracarboxylic anhydride in a molar ratio of 2:1; the diamine monomer is 4,4'-diaminodiphenylmethane;
[0119] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with an aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 1 mL / min; the stirring rate is 700 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;
[0120] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0121] A polyurethane coating comprises the following components in parts by weight:
[0122] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0123] Example 10
[0124] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0125] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0126] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is an acetic acid steam bath; the steam bath treatment time is 7 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%;
[0127] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.5:1; the polyamic acid content in the polyamic acid mixed solution is 4wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent is a mixture of N-methylpyrrolidone and dimethylformamide in a volume ratio of 1:1; the dianhydride monomer is a mixture of pyromellitic anhydride and 3,3',4,4'-biphenyltetracarboxylic anhydride in a molar ratio of 2:1; the diamine monomer is 4,4'-diaminodiphenylmethane;
[0128] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 3 mL / min; the stirring rate is 700 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;
[0129] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0130] A polyurethane coating comprises the following components in parts by weight:
[0131] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0132] Embodiment 11
[0133] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0134] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0135] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is an acetic acid steam bath; the steam bath treatment time is 7 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%;
[0136] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.5:1; the polyamic acid content in the polyamic acid mixed solution is 4wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent is a mixture of N-methylpyrrolidone and dimethylformamide in a volume ratio of 1:1; the dianhydride monomer is a mixture of pyromellitic anhydride and 3,3',4,4'-biphenyltetracarboxylic anhydride in a molar ratio of 2:1; the diamine monomer is 4,4'-diaminodiphenylmethane;
[0137] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with an aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 2 mL / min; the stirring rate is 700 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;
[0138] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0139] A polyurethane coating comprises the following components in parts by weight:
[0140] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0141] Comparative Example 1
[0142] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0143] (1) The natural cellulose raw material is processed to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm; the nanocellulose content in the deionized water dispersion of the nanocellulose is 1.2 wt%;
[0144] (2) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.5:1; the polyamic acid content in the polyamic acid mixed solution is 4wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent is a mixture of N-methylpyrrolidone and dimethylformamide in a volume ratio of 1:1; the dianhydride monomer is a mixture of pyromellitic anhydride and 3,3',4,4'-biphenyltetracarboxylic anhydride in a molar ratio of 2:1; the diamine monomer is 4,4'-diaminodiphenylmethane;
[0145] (3) Under stirring conditions, a polyamic acid mixed solution is injected into a deionized water dispersion of nanocellulose using a syringe with a nozzle; the nozzle is located below the liquid surface of the deionized water dispersion of nanocellulose; after the injection is completed, a chemical imidization agent is added to imidize the polyamic acid; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with a nozzle aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 2 mL / min; the stirring rate is 700 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;
[0146] (4) placing the injected mixed dispersion in an acidic steam bath environment for steam treatment, and then exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; wherein the acidic steam bath is an acetic acid steam bath; and the steam bath treatment time is 7 hours;
[0147] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0148] A polyurethane coating comprises the following components in parts by weight:
[0149] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0150] Comparative Example 2
[0151] A method for preparing a high-porosity interpenetrating network structure gel powder comprises the following steps:
[0152] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;
[0153] (2) placing a deionized water dispersion of nanocellulose in an acidic steam bath environment for steam treatment to obtain a nanocellulose hydrogel solution; wherein the acidic steam bath is an acetic acid steam bath; the steam bath treatment time is 7 hours; and the nanocellulose content in the nanocellulose hydrogel solution is 1.2 wt%;
[0154] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 1:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.5:1; the polyamic acid content in the polyamic acid mixed solution is 4wt%; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent is a mixture of N-methylpyrrolidone and dimethylformamide in a volume ratio of 1:1; the dianhydride monomer is a mixture of pyromellitic anhydride and 3,3',4,4'-biphenyltetracarboxylic anhydride in a molar ratio of 2:1; the diamine monomer is 4,4'-diaminodiphenylmethane;
[0155] (4) Under stirring conditions, a polyamic acid mixed solution is injected into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, a chemical imidization reagent is added; after standing, the solution is exchanged with a deionized water solvent to obtain a hydrogel having an interpenetrating network structure; the injection is performed using a 1 ml medical syringe, i.e., the nozzle has a nozzle with an aperture of 0.3 mm; the injection rate of the polyamic acid mixed solution is 2 mL / min; the stirring rate is 700 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;
[0156] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
[0157] A polyurethane coating comprises the following components in parts by weight:
[0158] 100 parts of waterborne polyurethane dispersion; 4 parts of high porosity interpenetrating network structure gel powder.
[0159] Performance test: The polyurethane coatings prepared in Examples 1-11 and Comparative Examples 1-2 were subjected to hardness test (GB / T6739-2006), paint film adhesion test (GB / T 5210-2006) and salt spray resistance test (GB / T1771-2007); the test results are shown in Table 1.
[0160]
[0161] Figure 2 and Figure 3 The following are scanning electron microscope images of the gel powder prepared in Example 11 and Comparative Example 1, respectively. Figure 2 It can be seen that the gel prepared by the solution internal injection method has a larger pore size, which greatly improves the porosity of the gel, is conducive to the full infiltration of the polyurethane material, improves the interface performance between the gel powder and the polyurethane resin, and further improves the mechanical strength and corrosion resistance of the coating. It shows that the polyimide nanofibers prepared by the injection method are more evenly dispersed in the nanocellulose, effectively preventing the occurrence of agglomeration. In Comparative Example 1, the nanocellulose gel solution was not prepared in advance, and the polyamic acid mixed solution was directly injected into the deionized water dispersion of the nanocellulose. The scattered nanocellulose could not play a "sickle"-like cutting role, but moved with the stirring like the polyamic acid; at the same time, Figure 2 It can be seen that the internally injected polyamic acid cannot precipitate a fiber structure, but plays the role of a bonding resin, making the nanocellulose stick together, reducing the porosity inside the gel, and the polyurethane cannot enter the gel, resulting in a decrease in the bonding force between the gel powder and the coating, which is not conducive to improving the coating performance. At the same time, in Comparative Example 2, due to the high viscosity of polyvinyl pyrrolidone, when its dosage is too high, it will affect the dispersion of polyamic acid in the nanocellulose hydrogel solution, which is not conducive to the formation of an interpenetrating network.
[0162] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.
Claims
1. A method for preparing a high-porosity interpenetrating network structure gel powder, characterized in that: The following steps are involved: (1) treating natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; (2) preparing a nanocellulose hydrogel solution by preparing a nanocellulose deionized water dispersion; (3) using diamine and dianhydride as raw materials to prepare a polyamic acid solution in an organic solvent, then adding polyvinyl pyrrolidone and stirring to obtain a polyamic acid mixed solution; the total weight mass ratio of polyvinyl pyrrolidone to the diamine and dianhydride raw materials is (0.01-0.5):1; the total weight mass ratio of nanocellulose to the diamine and dianhydride raw materials is (0.5-3):1; (4) Under stirring conditions, injecting the polyamic acid mixed solution into the nanocellulose hydrogel solution using a syringe with a nozzle; the nozzle is located below the liquid surface of the nanocellulose hydrogel solution; after the injection is completed, adding a chemical imidization reagent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-porosity interpenetrating network structure gel powder.
2. The method for preparing a high-porosity interpenetrating network structure gel powder according to claim 1, characterized in that: In step (2), the nanocellulose hydrogel solution is prepared by a steam bath method or an ion crosslinking method.
3. The method for preparing a high-porosity interpenetrating network structure gel powder according to claim 1, characterized in that: The nanocellulose content in the nanocellulose hydrogel solution of step (2) is 0.5-2wt%.
4. The method for preparing a high-porosity interpenetrating network structure gel powder according to claim 1, characterized in that: The polyamic acid content in the polyamic acid mixed solution of step (3) is 2-6wt%.
5. The method for preparing a high-porosity interpenetrating network structure gel powder according to claim 1, characterized in that: In step (4), the nozzle has 1 to 4 nozzles.
6. The method for preparing a high-porosity interpenetrating network structure gel powder according to claim 5, characterized in that: In step (4), the nozzle aperture is 0.1-1 mm.
7. The method for preparing a high-porosity interpenetrating network structure gel powder according to claim 1, characterized in that: In step (4), the injection rate of the polyamic acid mixed solution is 1-3 mL / min.
8. A high porosity interpenetrating network structure gel powder, characterized in that: The invention is prepared by the method for preparing a high-porosity interpenetrating network structure gel powder as described in any one of claims 1 to 7.
9. An application of a high-porosity interpenetrating network structure gel powder as claimed in claim 8, characterized in that: The high-porosity interpenetrating network structure gel powder is used in the field of polyurethane coatings.
10. A polyurethane coating, characterized in that: The invention comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion; and 0.5-5 parts of the high-porosity interpenetrating network structure gel powder according to claim 8.
Citation Information
Patent Citations
Environment-friendly antibacterial waterborne wood coating
CN107474680A
Preparation method of antibacterial coating used for paper
CN110105531A
Preparation method of high-elastic hydrophobic radiation curing wood paint skin feeling coating
CN117801653A
Modified aerogel powder as well as preparation method and application thereof
CN118667223A
Polyimide graphene gel powder as well as preparation method and application thereof
CN118702962A